Atlantic overturning responses to obliquity and precession over the last 3 Myr. (6th February 2014) - Lisiecki, L. E.
<x xml:space="preserve">Abstract</x> This study analyzes 39 Atlantic and seven Pacific benthic δ13C records to characterize obliquity and precession responses in Atlantic overturning since 3 Ma. Regional benthic δ13C stacks are also analyzed. A major transition in orbital responses is observed at 1.5–1.6 Ma coincident with the first glacial shoaling of Northern Component Water. Since ∼1.5 Ma, the phases of Atlantic benthic δ13C records from 2300 to 4000 m depth lag maximum obliquity by 59° (6.7 kyr) and June perihelion precession forcing by 133° (8.5 kyr). Comparison with North Atlantic sea surface temperature suggests that these orbital responses (particularly precession) in middle deep Atlantic δ13C are associated with changes in ocean heat transport and overturning rates. The mid‐Pleistocene transition had little effect on the obliquity and precession phases of benthic δ13C but did result in a ∼50% decrease in the obliquity power of middle deep Atlantic δ13C at 0.6 Ma.